2023
DOI: 10.1242/dev.201504
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory SMAD6 interferes with BMP dependent generation of muscle progenitor cells and perturbs proximodistal pattern of murine limb muscles

Abstract: The mechanism of pattern formation during limb muscle development remains poorly understood. The canonical view holds that naïve limb muscle progenitor cells (MPCs) invade a pre-established pattern of muscle connective tissue, thereby forming individual muscles. Here we show that early murine embryonic limb MPCs highly accumulate pSMAD1/5/9, demonstrating active signaling of bone morphogenetic proteins (BMP) in these cells. Overexpression of inhibitory SMAD6 in limb MPCs abrogated BMP signaling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition to OSR1, other transcription factors produced by CT fibroblasts have been shown to regulate limb muscle patterning during development, such as Tcf4 (now Tcfl2), belonging to the TCF/LEF family (Kardon et al, 2003), the T-box genes Tbx3 and Tbx5 (Hasson et al, 2010, Colasanto et al, 2016), and the homeobox Hoxa11 (Swinehart et al, 2013). However, Tcf4 and Hoxa11 are also expressed in muscle cells (Murphy et al, 2011, Asfour et al, 2023) or in muscle lineage (Flynn et al, 2023), where they could directly act on muscle patterning. It has been recently shown that a subpopulation of CT fibroblasts integrates muscle fibres at the muscle/tendon interface during development and postnatal stages (Esteves de Lima et al, 2021, Yaseen et al, 2021, Yan et al, 2022, Flynn et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to OSR1, other transcription factors produced by CT fibroblasts have been shown to regulate limb muscle patterning during development, such as Tcf4 (now Tcfl2), belonging to the TCF/LEF family (Kardon et al, 2003), the T-box genes Tbx3 and Tbx5 (Hasson et al, 2010, Colasanto et al, 2016), and the homeobox Hoxa11 (Swinehart et al, 2013). However, Tcf4 and Hoxa11 are also expressed in muscle cells (Murphy et al, 2011, Asfour et al, 2023) or in muscle lineage (Flynn et al, 2023), where they could directly act on muscle patterning. It has been recently shown that a subpopulation of CT fibroblasts integrates muscle fibres at the muscle/tendon interface during development and postnatal stages (Esteves de Lima et al, 2021, Yaseen et al, 2021, Yan et al, 2022, Flynn et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“… 20 In addition to OSR1, other transcription factors produced by CT fibroblasts have been shown to regulate limb muscle patterning during development, such as Tcf4 (now Tcf7l2), belonging to the TCF/LEF family, 21 the T-box genes Tbx3 and Tbx5, 22 , 23 and the homeobox Hoxa11. 24 However, Tcf4 and Hoxa11 are also expressed in muscle cells 25 , 26 or in muscle lineage, 27 where they could directly act on muscle patterning. It has been recently shown that a subpopulation of CT fibroblasts integrates into muscle fibers at the muscle/tendon interface during development and postnatal stages.…”
Section: Introductionmentioning
confidence: 99%
“…Two transcriptional readouts of YAP signalling, ANKDR1 and CTGF, are regionalized in tip myonuclei in foetal muscles, with an unknown function related to muscle/tendon interface [6]. BMP signalling (assessed with pSMAD1/5/9) in tip myonuclei has been suggested to be involved in fibroblast incorporation into myotubes at the MTJ and limb muscle patterning in chicken and mouse embryos [18], [25].…”
Section: Introductionmentioning
confidence: 99%